2017
DOI: 10.5301/uj.5000227
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-Specific Antigen Increase during Dutasteride to Indicate the Need for Prostate Biopsy: Influence of Prostatic Inflammation

Abstract: Treatment with dutasteride can help to analyze PSA kinetic. A persistent prostatic inflammation is a factor able to reduce the performance of PSA kinetic during dutasteride treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…PSA reduction was not significant predictor for prostate cancer detection in this study because this has already included as a subsequent biopsy criteria. Furthermore, one study from Italy reported about the relationship between PSA reduction by dutasteride and prostate cancer (Sciarra et al, 2017). They showed that PSA reduction after 6 months of treatment was not a significant indicator, but persistent prostatic inflammation found by prostate biopsy is the important predictor (Sciarra et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…PSA reduction was not significant predictor for prostate cancer detection in this study because this has already included as a subsequent biopsy criteria. Furthermore, one study from Italy reported about the relationship between PSA reduction by dutasteride and prostate cancer (Sciarra et al, 2017). They showed that PSA reduction after 6 months of treatment was not a significant indicator, but persistent prostatic inflammation found by prostate biopsy is the important predictor (Sciarra et al, 2017).…”
Section: Discussionmentioning
confidence: 99%